Industrielle Cluster als Ursache regionaler Prosperität? Zur Konvergenz deutscher Arbeitsmarktregionen 1996–2005 - Kubis, Alexander; Brachert, Matthias; Titze, Mirko (Raumforschung und Raumordnung | Spatial Research and Planning, 2009)
This paper explores the impact of industrial clusters on regional growth at level of Germany’s functionally defined labour market regions (AMR) within a regional convergence model. It focuses especially on the role of the co-location of vertically connected industrial sectors. Based on works of Schnabl (2000) it is possible to identify three different effects of industrial clusters on regional economic performance. Beside the effect of regionally concentrated economic sectors (horizontal clusters) and value adding chains (vertical clusters) on the region itself, we are able to control for regional spillover effects of industrial clusters. Further, the study allows the isolated examination of the impact of industrial cluster while taking regional convergence into consideration. It is possible to demonstrate positive growth effects of industrial clusters along with an overall process of convergence as same as with a specific eastern one. Therefore industrial cluster present an opportunity to explain deficits within the process of East-West-Convergence. Their relative absence of industrial clusters in Eastern Germany influences the growth potential in a negative way.